Welche Konsequenzen ziehen Mathematiklehrkräfte aus verpflichtenden Diagnose- und Vergleichsarbeiten? Ergebnisse einer Interviewstudie (mathematica didactica, 2007)
This paper analyzes how and to what extent math teachers draw instructional conclusions from state mandated school performance tests that aim to encourage data-based school improvement. The interview study approached elementary and secondary school teachers (n = 50) in Baden-Württemberg, one of the larger German states. Mostly sobering results of the qualitative content analysis show that a single math test after a two-year learning period cannot provide sufficient information for better understanding students' mathematical knowledge acquisition. Only a minority of the teachers explained that some test assignments prompted reflection about slightly changing their instructional approach. The paper concludes with a discussion on the characteristics of the testing and feedback system in Baden-Württemberg and its potential impact on the schools' disapproval to make sensible use of the test results.